Factor the following trinomial:
![Factor the following trinomial class=](https://us-static.z-dn.net/files/d67/bb6661b1ffa8070f558441fee0f1f1ce.png)
Answer:
D
Step-by-step explanation:
Given
n² - n - 42
Consider the factors of the constant term (- 42) which sum to give the coefficient of the n- term (- 1)
The factors are - 7 and + 6 , since
- 7 × + 6 = - 42 and - 7 + 6 = - 1 , then
n² - n - 42 = (n - 7)(n + 6) ← in factored form
Solution :-
Given,
We need to factorise it.
So let's start !!
Two factors are -7 and 6.
Therefore,